Psychological status of patients with breast cancer following radiation therapy - G. A. Tkachenko; I. A. Gladilina; A. M. Stepanova; A. M. Shabanov; I. V. Vysozkaya; E. S. Makarov; N. R. Molodikova (ABV-press, 2018)
This article discusses clinical and psychological examination of 54 patients with stages I-IIA breast cancer after organ-sparing surgery and postoperative radiotherapy. Our results suggested that approximately half of the patients (51.9 %) had a significant increase in anxiety 6 months after completion of radiotherapy, whereas 40.4 % of women had mild depression.